The EC50 of remifentanil to minimize the cardiovascular changes during head holder pinning in neurosurgery - Do, Wang Seok; Kim, Tae Kyun; Kim, Hae Kyu; Kim, Cheul Hong (Korean journal of anesthesiology, 2012)
Background: During neuroanesthesia, head holder pinning commonly results in sympathetic stimulation manifested by hemodynamic changes, such as increased heart rate and arterial blood pressure. Remifentanil has been used successfully to control acute autonomic responses during neurosurgical procedures. The objective of this study was to determine effect-site concentration of remifentanil for suppressing the hemodynamic response to head holder pinning with the probability of 50% (EC50). Methods: Forty-one ASA physical status I or II patients, between the ages of 20-70, who were scheduled for neurosurgery were recruited into this study. After arrival in the operating room, standard monitoring was applied throughout the study, which included a bispectral index monitor. Both propofol and remifentanil were administered by Target-control infusion device. The Dixon "up-and-down" sequential allocation method was used to determine the EC50 of remifentanil. Results: The EC50 of remifentanil was 2.19 ± 0.76 ng/ml by the turning point estimate (TPE). In probit analysis, EC50 was 2.42 ng/ml (95% CI : -0.62-4.66) and EC95 was 5.70 ng/ml (95% CI : 4.02-67.53). The EC50 estimator comes from isotonic regression is 2.90 ng/ml (95% CI : 1.78-3.65). The EC95 estimator comes from isotonic regression is 4.28 ng/ml (95% CI : 3.85-4.41). Conclusions: This study showed that EC50 of remifentanil was 2.19 ± 0.76 ng/ml by TPE. EC50 was 2.42 ng/ml (95% CI -0.62-4.66) in probit analysis, as back up analysis. The EC50 estimator comes from isotonic regression is 2.90 ng/ml (95% CI : 1.78-3.65). KCI Citation Count: 0